2010
DOI: 10.1038/ejcn.2010.74
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y gene polymorphisms are not associated with obesity in a South Indian population

Abstract: Background/Objectives: Neuropeptide Y (NPY) gene has been shown to have a critical role in the regulation of satiety, reproduction, central endocrine and cardiovascular systems. Among the primary functions associated with NPY are its acute effects on feeding behavior and energy expenditure. The aim of this study is to evaluate the relationship between obesity and NPY gene polymorphisms in a South Indian Population. Subjects/Methods: Three polymorphisms in NPY gene (Leu7Pro, Ser50Ser and A7735G) were analyzed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…DISCUSSION Association of NPY gene Leu7Pro polymorphism with obesity has been studied in many populations and conflicting results were obtained. Several studies found no association with obesity results (ROCHE et al, 1997;BHASKAR et al, 2010;DING et al, 2003;KARVONEN et al, 1998), while several others found association but with different aspects of obesity. In a study Pro7 allele has been associated with lower BMI values as well as lower WHRs in women respectively (MATTEVİ et al,2002;MUTSCHLER et al, 2013), while in another two studies it was associated with increased BMI values (van ROSSUM et al, 2006;DING et al, 2005) and increased risk of obesity (YEUNG et al, 2011).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…DISCUSSION Association of NPY gene Leu7Pro polymorphism with obesity has been studied in many populations and conflicting results were obtained. Several studies found no association with obesity results (ROCHE et al, 1997;BHASKAR et al, 2010;DING et al, 2003;KARVONEN et al, 1998), while several others found association but with different aspects of obesity. In a study Pro7 allele has been associated with lower BMI values as well as lower WHRs in women respectively (MATTEVİ et al,2002;MUTSCHLER et al, 2013), while in another two studies it was associated with increased BMI values (van ROSSUM et al, 2006;DING et al, 2005) and increased risk of obesity (YEUNG et al, 2011).…”
Section: Resultsmentioning
confidence: 97%
“…Association between NPY gene variants and obesity and certain obesity-related phenotypes have been studied in many populations and different findings were obtained. Two studies carried out by Roche et al in French morbidly obese cases and Bhaskar et al in Indian population have found no evidence supporting the association (ROCHE et al, 1997;BHASKAR et al, 2010). In another study carried out in a population from Brasil have observed that NPY Leu7Pro variant was accounted for the decrease in BMI in premenapousal women (MATTEVİ et al, 2002).…”
mentioning
confidence: 92%
“…98 However, other studies reported the rs16139 polymorphism to not be associated with weight gain in Finnish youth, 99 does not reproducibly associate with BMI in several populations, 100 and is not associated with obesity in an South Indian cohort. 101 A 2015 meta-analysis of 6 case-controlled studies of the rs16139 SNP indicated that the Leu to Pro polymorphism is associated with an increased risk of obesity. 91 Two silent mutations (rs9785023 and rs5574), one of which located within the active form of NPY (rs9785023) have been investigated, although neither SNP was associated with obesity.…”
Section: Orexigenic Neuropeptidesmentioning
confidence: 99%
“…NPY polymorphism rs16139 has been found to be associated with alterations in the synthesis and secretion of NPY [34], higher serum levels of total and LDL cholesterol in obese subjects [35], coronary artery atherosclerosis [36], insulin resistance and risk for type II diabetes [37], plasma levels of inflammatory molecules and NPY in diabetes patients [38], and metabolic syndrome [39]. The association between rs16139 and risk of obesity is inconclusive [29,[40][41][42][43]. Some findings of other NPY gene polymorphisms have also been reported.…”
Section: Introductionmentioning
confidence: 99%